PENGARUH PENERAPAN TEKNIKQUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 13 PADANG TAHUN PELAJARAN 2013/2014 - Sundari Utami, Silvia; Rismen, Sefna; febriana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was conducted due to the studentsâ low understanding on mathematics concept in class XI IPA of SMAN 13 Padang. This was intended to reveal whether the use of Quick on the Draw technique could improve the studentsâ understanding on mathematics concept better than that of the conventional learning. This was an experimental class. The population of the research was all of students in class XI IPA of SMAN 13 Padang registered in Academic Year 2013/2014. The data was collected by administering a test whose reliability was 0,858. The result of hypothesis test indicated that P-value = 0,014 < Î± (0,05) meaning that the hypothesis was accepted. At last, it was concluded that the use of Quick on the Draw technique could improve the studentsâ understanding on mathematics concept better than that of the conventional learning.